Preparation and Properties of 5-Fluorouracil-Loaded Chitosan Microspheres for the Intranasal Administration - Li, Wanqing; Ba, Hongyuan; Huang, Peng; Zheng, Aiping; Yang, Xi (Drug Research, 2018)
Objective To study the preparation technique of 5-fluorouracil and the release characteristic of 5-fluorouracil-loaded chitosan microspheres for the intranasal administration.Methods 5-fluorouracil-loaded chitosan microspheres were prepared by emulsion chemical cross-link technique. The orthogonal experimental design was used to optimize the preparation procedure. Dynamic dialysis method was applied to determine the release characteristic of microspheres in vitro and its influencing factors. Swelling behavior was expressed by swelling ratio. The degree of mucoadhesion was investigated by determining the mucociliary transport rate(MTR) of the microparticle across a frog palate.Results Microspheres with a good shape and narrow size distribution were prepared. The average diameter was 43±4 μm. The drug loading was (38.5±1.0) %. The entrapment efficiency was (79.0±1.8) %. The drug release profile in vitro could be described by Higuichi eqution as Q=0.1035t1/2+0.0284 (r=0.9965). Chitosan had good mucoadhesive property and caused a significant reduction in MTR(P<0.01).Conclusion The optimized technique has a good reproducibility and a high entrapment efficiency, so it could be used to prepare 5-fluorouracil-loaded chitosan microspheres for the intranasal administration.Chitosan is a good material for nasal preparation and has prospective development in the pharmaceutical field.
Keywords: flourouracil: chitosan; microspheres; drug carriers